Insights from stratigraphic reconfiguration induced by the South Pole-Aitken massive impact - Sheng Gou; Zongyu Yue; Yangting Lin; Bin Su; Zhanchuan Cai; Roberto Bugiolacchi; Kaichang Di; Patrick C. Pinet; Yuyang He; Honglei Lin; Hengci Tian; Sen Hu; et al. (Icarus, 2026)

Polygonatum kingianum polysaccharides ameliorate cognitive impairments in alcohol-exposed obese mice in a sex-specific manner by regulating the gut microbiome and metabolome - Jiayao Lv; Yizhe Qu; Qixin Yan; Ken Cheng; Qingyang Wu; Jiayi Zhang; Xinting Duan; Shanshan Han; Honglei Tian; Lin Shi (Food Research International, 2026)

Element substitution engineering of Li3VO4: Exposing high-activity (110) facets for stable interface and superior lithium storage - Huan Liu; Zhaozhao Han; Honglei Zhao; Andong Lin; Dan Zhang; Huaifang Zhang; Jianchuan Wang; Yuanyuan Feng (Chemical Engineering Journal, 2026)

Dynamic World Temporal Probability Aggregation for High-Resolution Ecosystem Service Monitoring in Tropical Tanzania - Sihan Meng; Manlin Wang; Huali Lin; Xinyue Zhang; Honglei Zhang (International Journal of Environmental Research, 2026)

Quantitative assessment of factors affecting reflectance retrieval from spectroscopic radiance images - Sheng Gou; Zongyu Yue; Bin Xie; Zhanchuan Cai; Honglei Lin; Yangting Lin; Kaichang Di (Advances in Space Research, 2026)

Aeolian transport of evaporite minerals in Utopia Planitia: insights from Qaidam Basin spectral analogs - Jianxun Shen; Honglei Lin; Zhaopeng Chen; Xue Guo; Yuqi Wang; Yizhong Zhang; Li Liu; Chengxiang Huang; Enze Wang; Rui Chang; Xuesen Xu; Zhicheng Cui; et al. (Science Bulletin, 2026)

CYP4B1 inhibits lung adenocarcinoma metastasis by downregulating slug transcription via Sp1 - Sijia Wang; Yijie Liu; Yuan Yu; Shuwei Ren; Weiwei Lin; Kemeng Qiang; Haishan Huang; Honglei Jin (Clinical & Experimental Metastasis, 2026)

Comparative study on pollution characteristics and ecological risk in Xiangshan Bay and its adjacent eastern sea area - Yanxia Wang; Honglei Jiang; Shengwei Xu; Xuelei Wang; Weiliang Shen; Lin Huang; Haihang Wang; Yuan Sun (Marine Pollution Bulletin, 2026)

Weak GPS signal tracking using block coherent integration based on NN discriminator - Zhiqiang Gong; Honglei Lin; Zhe Liu; Gang Ou (GPS Solutions, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

A novel method of estimating phytoplankton absorption coefficient for inland waters based on OLCI using Sun-induced chlorophyll-a fluorescence - Wenyu Liu; Yiling Zheng; Jie Lin; Yunmei Li; Honglei Guo; Huaiqing Liu; Yuxin Zhu; Fangfang Chen; Heng Lü; Song Miao (Journal of Oceanology and Limnology, 2026)

A review of researches on carbon dioxide emission accounting and evaluation - Feng Lin; Honglei Ding; Wenhuan Wang; Chaojie Wei; Fan Han; Yifeng Xu; Ziyi Zhang; Jie Song; Weiguo Pan (Environment, Development and Sustainability, 2026)

Oncogenic and immunological roles of LAMP5 across cancers and its potential utility in bladder cancer - Zhenni Lin; Kun Zhao; Sijia Wang; Jianting Liu; Yijie Liu; Kemeng Qiang; Mingzhi Huang; Ning Sun; Peipei Zhang; Yan Hu; Yongyong Lu; Honglei Jin (Apoptosis, 2026)

Multiple-level fault controlled hydrothermal system in Huangshadong, Southeast China: Insights from coupled geophysical and geochemical investigations - Lu Liu; Xianan Qin; Zheng’an Wei; Min Zhang; Honglei Shi; Xiting Long; Wenjing Lin; Mingxiang Qiu; Guiling Wang; Shihua Qi; Fei Liu (Geothermics, 2026)

AI-driven framework for high-precision seamless sunshine duration estimation using Himawari-8 satellite and ground observations - Honglei Wu; Zhaohua Liu; Zhaoliang Zeng; Ke Gui; Zhijian Lin; Peng Xie; Ruqing Zhu; Zhehao Liang; Yaqiang Wang; Huizheng Che (Atmospheric Research, 2026)

One-year observation of cloud condensation nuclei concentration in a coastal city in eastern China: Seasonal variations, wet deposition, and regional transport - Zihan Wang; Yishu Bian; Qing Duan; Honglei Wang; Zihao Wu; Yue Ke; Tianliang Zhao; Wen Lin (Science of The Total Environment, 2025)

UPRS-1: A regolith simulant of Utopia Planitia, Mars - Yiming Diao; Honglei Lin; Juan Li; Shouding Li; Changyi Xu; Zhaobin Zhang; Zongyu Yue; Bo Zheng; Xiukuo Sun; Tao Xu; Xinshuo Chen; Yanfang Wu; et al. (Icarus, 2025)

Multi-omics approaches provide insights into adaptation to low salinity of intertidal clams - Zihan Lin; Honglei Wang; Geqi Gao; Hongtao Nie; Kai Ye; Donghong Niu; Jiale Li (Marine Environmental Research, 2025)

Mechanistic insights into cross-modal aroma-taste interactions mediating sweetness perception enhancement in Fu brick tea - Zhihui Hu; Amr M. Bakry; Lin Shi; Ping Zhan; Wanying He; Walaa A.M. Eid; Hussein Ferweez; Yahya S. Hamed; Hesham A. Ismail; Honglei Tian; Peng Wang (Food Chemistry, 2025)

Preparation of W/W emulsion gels based on chitosan and carboxymethyl cellulose via associative phase separation - Jinfeng Zhao; Dehui Lin; Runguang Zhang; Di Wang; Aiqing Zhao; Honglei Tian; Xingbin Yang (Food Hydrocolloids, 2025)

Double-confined FeCo nanoalloys as efficient and stable catalyst for selective hydrogenation of nitroarenes - Zhenyu Lei; Hao Sun; Lin Wu; Honglei Sun; Xiaomin Yang; Jingyao Liu; Peng Zhang; Mingjun Jia (Chemical Engineering Journal, 2025)

Green remediation, mechanisms, and pathways of synthetic phenolic antioxidants by Fe-based antioxidant combined ball milling - Fei Lin; Honglei Ren; Fengtao Sun; Xiaoxue Pan; Xuesheng Zhang (Chemical Engineering Journal, 2025)

Temporal variations in black carbon in the Yangtze River Delta of China: Long-term observations and trends under different pollution processes - Jianhao Ren; Honglei Wang; Yue Tan; Wenjie Wang; Bin Zhu; Tianliang Zhao; Wen Lin; Duanyang Liu; Lijuan Shen; Shuangshuang Shi (Atmospheric Research, 2025)

Rakicidin J and K, two cytotoxic and antibacterial cyclic depsipeptides from the marine bacterium Micromonospora chalcea - Li Chen; Lijun Xie; Jian Zhou; Dongsheng Fang; Honglei Jiang; Wei Liu; Yuqiu Ye; Wei Zhao; Hong Jiang; Feng Lin (Natural Product Research, 2025)

Three new compounds from the seeds of Sinapis alba L - Degang Kong; Chuanhou Li; Liang Ding; Zhenhua Tian; Lu Wang; Xue Liu; Qinghe Kong; Honglei Zhou; Lin Liao (Natural Product Research, 2025)

Upper limit of ice content at the lunar south pole as revealed by the Earth-based SYISR–FAST bistatic radar system - Mingyuan Li; Jinghai Sun; Xin’an Yue; Honglei Lin; Zhiqing Chen; Feng Ding; Baiqi Ning; Yong Wei; Chi Wang; Peng Jiang (Science Bulletin, 2025)

Thin basaltic regolith at the Chang'e-6 landing site - Sheng Gou; Zongyu Yue; Yangting Lin; Kaichang Di; Patrick C. Pinet; Wei Yang; Yuyang He; Yi Chen; Roberto Bugiolacchi; Hengci Tian; Honglei Lin; Sen Hu (Earth and Planetary Science Letters, 2025)

Application of machine learning to predict the fluoride removal capability of MgO - Lin Fan; Dexi Wang; Honglei Yu; Ze Gong; Yan He; Jinyuan Guo (Journal of Environmental Chemical Engineering, 2025)

A case study of numerical simulation on the interaction among random waves, double caisson composite breakwater and seabed - Junwei Liu; Lin Cui; Yunping Jia; Honglei Sun (Ocean Engineering, 2025)

Chronic exposure to hexavalent chromium induces esophageal tumorigenesis via activating the Notch signaling pathway - Yilin Zhu; Fanrong Liu; Lei Liu; Jinfu Wang; Fengyuan Gao; Lan Ye; Honglei Wu; Chengjun Zhou; Guimei Lin; Xiaogang Zhao; Peichao Li (Journal of Zhejiang University-SCIENCE B, 2025)

Higher water content observed in smaller size fraction of Chang'e-5 lunar regolith samples - Honglei Lin; Rui Xu; Shuai Li; Rui Chang; Hejiu Hui; Yang Liu; Hengci Tian; Kai Fan; Zhiping He; Huaiyu He; Wei Yang; Yangting Lin; et al. (Science Bulletin, 2024)

Complex basalt evolution in the Chang'e-6 landing area - Sheng Gou; Zongyu Yue; Yangting Lin; Kaichang Di; Patrick C. Pinet; Roberto Bugiolacchi; Yuyang He; Wei Yang; Honglei Lin; Hengci Tian; Sen Hu (Earth and Planetary Science Letters, 2024)

Aircraft observation of aerosol and mixed-phase cloud microphysical over the North China Plain, China: Vertical distribution, size distribution, and effects of cloud seeding in two-layered clouds - Zihan Wang; Honglei Wang; Xiaobo Dong; Yang Yang; Yue Ke; Sihan Liu; Yi Cui; Kun Cui; Zihao Wu; Wen Lin (Atmospheric Research, 2024)

In-situ aircraft observations of aerosol and cloud microphysical characteristics of mixed-phase clouds over the North China Plain - Kun Cui; Honglei Wang; Yue Ke; Xiaobo Dong; Yang Yang; Zihao Wu; Sihan Liu; Zihan Wang; Wen Lin; Tianliang Zhao (Science of The Total Environment, 2024)

Heparin mimicking sulfonated polyester synergistically promotes bacterial Infected-Wound healing with ROS responsive cinnamaldehyde based prodrugs - Haiwei Liu; Pengfei Shan; Yingwen Lu; Xiaoyue Lian; Feng He; Jinxiang Xiao; Linan Qiu; Zhenghao Liu; Zuobin Gan; Qingshan Yan; Yupeng Qiu; Wenwen Lin; et al. (Chemical Engineering Journal, 2024)

Carbon dioxide-focused greenhouse gas emissions from petrochemical plants and associated industries: Critical overview, recent advances and future prospects of mitigation strategies - Yuxin Yan; Yoong Xin Pang; Xiang Luo; Qingyang Lin; Cheng Heng Pang; Honglei Zhang; Xiang Gao; Tao Wu (Process Safety and Environmental Protection, 2024)

Assessing the modulation of outer bank erosion by slump blocks: A case study from Marqu Meadow, China - Lei Liu; Lekui Zhu; Dong Chen; Qihua Ran; Honglei Tang; Jun Yan; Lin Liu (Geomorphology, 2024)

Return to the Moon: New perspectives on lunar exploration - Yangting Lin; Wei Yang; Hui Zhang; Hejiu Hui; Sen Hu; Long Xiao; Jianzhong Liu; Zhiyong Xiao; Zongyu Yue; Jinhai Zhang; Yang Liu; Jing Yang; et al. (Science Bulletin, 2024)

Two new rakicidin derivatives from marine Micromonospora chalcea FIM-R160609 - Li Chen; Lijun Xie; Wei Zhao; Jian Zhou; Honglei Jiang; Wei Liu; Hong Jiang; Feng Lin (Natural Product Research, 2024)

Impacts of the aerosol mixing state and new particle formation on CCN in summer at the summit of Mount Tai (1534m) in Central East China - Zihao Wu; Honglei Wang; Yan Yin; Lijuan Shen; Kui Chen; Jinghua Chen; Zhongxiu Zhen; Yi Cui; Yue Ke; Sihan Liu; Tianliang Zhao; Wen Lin (Science of The Total Environment, 2024)

Analysis of pollutant dispersion patterns in rivers under different rainfall based on an integrated water-land model - Fei Lin; Honglei Ren; Jingsha Qin; Manqi Wang; Ming Shi; Yucheng Li; Rujing Wang; Yimin Hu (Journal of Environmental Management, 2024)

Numerical Analysis of Dynamic Response and Liquefaction Phenomena in Sandy Seabed Foundation around a Semi-Circular Breakwater under Wave Loading - Junwei Liu; Yunping Jia; Lin Cui; Honglei Sun; Xu Lv; Mohsen Saleh Asheghabadi (Journal of Marine Science and Engineering, 2023)
Understanding the stability of the seabed foundation holds paramount significance in guaranteeing the safety and structural soundness of the breakwater alongside additional offshore structures. This study aimed to investigate the stability of a sandy seabed foundation around a semi-circular breakwater under wave loading in nearshore areas. A coupled numerical model of waves, a semi-circular breakwater, and the seabed was developed based on the OpenFOAM platform. The VARANS equations were used to govern the wave behavior. Meanwhile, the Biot’s partially dynamic model was employed to numerically simulate the seabed response considering both consolidation under self-weight and dynamic response under wave loading. The effects of various wave parameters, seabed properties, and the radius of the structure on the dynamic response of the seabed and the depth of liquefaction were investigated. The numerical results indicate that an increase in wave height, period, and permeability coefficient intensifies the dynamic response of the seabed soil. Furthermore, an increase in water depth weakened the soil’s dynamic response. There was a negative correlation between the radius of the semi-circular breakwater and the dynamic response. The influence of Poisson’s ratio on the dynamic response of the seabed was relatively small. Furthermore, a stronger dynamic pore pressure response was observed at the connection between the semi-circular breakwater and the rubble foundation.

Mineralogical evidence of water activity in the northern lowlands of Mars based on inflight-calibrated spectra from the Zhurong rover - Honglei Lin; Yangting Lin; Yong Wei; Sheng Gou; Chi Zhang; Renhao Ruan; Yongxin Pan (Science China Earth Sciences, 2023)

Optical properties and molecular composition of wintertime atmospheric water-soluble organic carbon in different coastal cities of eastern China - Haibiao Chen; Caiqing Yan; Qinglong Fu; Xinfeng Wang; Jiao Tang; Bin Jiang; Honglei Sun; Tiancheng Luan; Qiaoyun Yang; Qianbiao Zhao; Jun Li; Gan Zhang; et al. (Science of The Total Environment, 2023)

A classification-based approach to mapping particulate organic matter (POM) in inland water using OLCI images - Huaiqing Liu; Wenyu Liu; Jie Lin; Heng Lyu; Yunmei Li; Fangfang Chen; Ying Zhao; Jiafeng Xu; Honglei Guo (Environmental Science and Pollution Research, 2023)

Phytochemical and chemotaxonomic investigations on the aerial parts of Cynanchum auriculatum Royle ex Wight - Yanling Xu; Chenyang Wu; Lu Wang; Shengbo Wu; Yueru Chen; Xiaoxue Ding; Lin Wang; Yi Yu; Weiming Du; Yuqing Zhang; Rachel Y.H. Yang; Jian Hong; et al. (Biochemical Systematics and Ecology, 2023)

Chemical constituents from the flowers of Cynanchum auriculatum Royle ex Wight - Xiaoxue Ding; Lu Wang; Yanling Xu; Shengnan Zheng; Shuang Wang; Lin Wang; Miao Qin; Shengbo Wu; Yi Yu; Jian Hong; Honglei Zhou; Lingchuan Xu; et al. (Biochemical Systematics and Ecology, 2023)

Assessment of factors affecting the diurnal variations of atmospheric PAHs based on a numerical simulation - Zhongxiu Zhen; Yan Yin; Haowen Zhang; Jingyi Li; Jianlin Hu; Lin Li; Xiang Kuang; Kui Chen; Honglei Wang; Qingyuan Yu; Xin Zhang (Science of The Total Environment, 2023)

Comparison of groundwater hydrogeochemistry of karst areas in northern and southern China with emphasis on their performance in karst development - Peng Yuming; Xiao Qiong; Xue Honglei; Lv Minghui; Lin Guangqi; Zhao Haijuan; Wu Peiyan; Guo Yongli (Carbonates and Evaporites, 2022)

Progress in Intradermal and Transdermal Gene Therapy with Microneedles - Ting Zhu; Wenya Zhang; Pengju Jiang; Shuwen Zhou; Cheng Wang; Lin Qiu; Honglei Shi; Pengfei Cui; Jianhao Wang (Pharmaceutical Research, 2022)

Involvement of cytokinin response regulator RhRR1 in the control of flowering - Lin Wu; Ming Feng; Yangchao Jia; Honglei Li; Yiqing Liu; Yusong Jiang (Acta Physiologiae Plantarum, 2019)

Robust multiple update-rate Kalman filter for new generation navigation signals carrier tracking - Honglei Lin; Yangbo Huang; Xiaomei Tang; Zhibin Xiao; Gang Ou (GPS Solutions, 2018)

Biocatalytic resolution of benzyl glycidyl ether and its derivates by Talaromyces flavus: effect of phenyl ring substituents on enantioselectivity - Chun Wei; Yunyun Chen; Honglei Shen; Shan Wang; Lin Chen; Qing Zhu (Biotechnology Letters, 2012)